Treatment of Outliers to Study Railway Vibrations Transmission (2012)
This paper presents the data analysis of the vibration induced by the propagation of waves caused by passing trains, metro and tram. These data are taken with an optical ﬁber accelerometer within the framework of the research project TRAVIESA (Transmisión de Vibraciones del ferrocarril urbanoal entorno: Estrategias, Tecnologías y materiales para su atenuación) fundedby CDTI and the Ministry of Science and Innovation of the Government of Spain. The methodology was developed to characterize the level of vibrations that aﬀect diﬀerent elements of railway infrastructure and nearby buildings. Optical ﬁber accelerometers were used and the measurements were made by the Technological Institute of Optics, Colour and Imaging (AIDO).